Curriculum Development Integrating Qur'anic Values and Character Education: A Study of Dialogic Communication in Q.S. Ash-Shaffat (37):102 - Alhamuddin Alhamuddin; M. Syukri Ismail (Program Pascasarjana Universitas Ibrahimy, 2025)
This study explores the integration of Qur'anic values, particularly those found in Q.S. Ash-Shaffat (37):102, into curriculum development and educational practices. The primary aim is to investigate how values such as patience (ṣabr), consultation (shūrā), conscious obedience (ṭāʿah), trust in God (tawakkul), and sincerity (ikhlāṣ) can be incorporated into educational frameworks to promote both academic and moral development. The research adopts a qualitative approach, focusing on document analysis and curriculum review as the primary data collection methods. Relevant educational documents, including curriculum frameworks, syllabi, textbooks, and policy guidelines, are analyzed to identify how these Qur'anic values are integrated across various subjects. The data is analyzed using thematic analysis to identify patterns and themes related to the presence and application of Qur'anic values in the curriculum. The results show that while some curricula explicitly include character education, others may implicitly reflect these values, emphasizing the importance of ethical conduct, reflection, and consultation in learning environments. The study concludes that the integration of Qur'anic values can significantly enhance the development of students' intellectual, emotional, and moral faculties. These values can transform the learning environment into one that nurtures holistic development, fostering ethical decision-making and resilience among students. The study recommends that educational institutions consider embedding Qur'anic values more systematically into curricula, not only within Islamic studies but across all subjects, to foster a comprehensive, character-driven education. Further research is suggested to explore the practical challenges and opportunities of implementing such a curriculum model in diverse educational contexts.